1977
DOI: 10.1093/bja/49.9.887
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-B Virus Infection in Anaesthetists

Abstract: To determine whether anaesthetists are at risk from developing hepatitis-B virus (HBV) infection from their patients, 95 anaesthetists working with black South Africans (who have a high prevalence of hepatitis-B antigenaemia) were questioned about attacks of viral hepatitis and their blood was tested for hepatitis-B (surface) antigen (HBsAg) and antibody (Anti-HBs). Anti-HBs was detected in the serum of 17.9% of the anaesthetists, but none was a chronic carrier of HBsAg. Two anaesthetists had suffered from acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…People working in hemodialysis units, oncology wards, blood laboratories, etc. are said to be at an increased risk of acquiring the infection (2,12,15). Several studies using serological markers of hepatitis B virus have shown a significant positive association between blood exposure and seropositivity of hospital employees (11).…”
Section: Introductionmentioning
confidence: 99%
“…People working in hemodialysis units, oncology wards, blood laboratories, etc. are said to be at an increased risk of acquiring the infection (2,12,15). Several studies using serological markers of hepatitis B virus have shown a significant positive association between blood exposure and seropositivity of hospital employees (11).…”
Section: Introductionmentioning
confidence: 99%